PENYABAB SISWA PUTUS SEKOLAH DI NAGARI LUBUK KARAK KECAMATAN SEMBILAN KOTO KABUPATEN DHARMASRAYA - Lonawati, Despi; Sano, Afrizal; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
a phenomenon in the field is the found that some students dropped out of school. The researcher was interested to concern about: causes of studentsâ dropout in NagariLubukKaraksubdistrict of Sembilan Koto district of Dharmasraya. Thepurposes of this research are to describecauses ofstudens dropouts related to (1) school, (2) economic factors, (3) family environmental factors.(4) contemporary friends,and (5) personal problems.This research is a descriptiveresearch sought to describecauses of studentsâdropout . The population of this research was all students who have dropped out of which totaled 35 people. Techniquetake the sample is total sampling.The instrument used was a questionnaire.The results of this research revealed that:42,9%studentsâ dropoutsto causes of economic factors, 30,0%contemporary friends, 18,7% personal problems, 17,1%school and14,1%family environmental factors. Based on the results of this research,researcher suggests to.Government officials look for a solution for students who dropping out of school by organizing package.Organizer of study program of guidance and counseling STKIP PGRI West Sumatera, in order to create a prospective counselors who not only served in school but also can serve student dropout of school.